Mycoplasma contamination of cell cultures maintained in laboratories of private, government and college institutions - Miyaki, Cosue; Pral, Michel Marie; Gallina, Neusa Maria Frazatti; Rizzo, Edda de (Revista de Saúde Pública, 1989)
Mycoplasma is one of the most serious contaminants of cell cultures. Its detection is very important in virology, as well as its eradication. The aim of this study was to verify the incidence of mycoplasma in cell lines maintained in seven laboratories of private, government and college institutions of the State of São Paulo, Brazil, for the purposes of research, production of reagents for diagnosis and production of biologicals for human and animal use. Of the 29 cell lines, eight were derived from human tissues and 21 from other animal species (dog, rabbit, mouse, hamster, monkey, pig, chicken and ox). Using the direct method with specific liquid and solid media for detection of mycoplasma, 48 out of the 106 cell samples tested were positive, corresponding to a contamination index of 45.28%. The incidence of contamination among the 35 cell samples of human origin was 51.43% (18 positive). Of the 71 samples originated from other species, 30 were positive (42.25%). The high incidence of contamination found calls for the adoption of measures for the prevention of this hazard: the elimination of mouth pipetting, the use of aseptic techniques and a rigid control of trypsin, serum and other components of cell culture media. The substitution of mycoplasma-free cultures for all contaminated ones and the performance of periodical tests for mycoplasma detection must also be carried out to prevent and avoid the dissemination of these organisms. Data obtained showed that contamination appeared in the 2nd (72.92%), in the 3rd (20.83%) and in the 4th passage (6.25%). By using this technique, five passages are sufficient to detect mycoplasma and allow a safety margin, thus shortening the length of the test, saving reagents and providing satisfactory and reliable results. If a similar study were carried out establishing five as the number of serial passages for each mycoplasma detection test, the original number of passages would be reduced from 848 to 530 and the time spent on the test would be reduced from eight weeks to five.